Interrupción temporal de la lactancia (ITA) y presentación de estro en vacas cebú posparto - Mahecha, Liliana; Henao, Damary; Cardona, Mariluz; Olivera A., Martha (Revista Colombiana de Ciencias Pecuarias, 2016)
Resumen Este estudio se llevó a cabo en vacas cebú amamantando bajo condiciones de trópico bajo, pastoreando brachiaria en condiciones semintensivas y con días abiertos mayores a 150. Con el fin de determinar si la interrupción temporal del amamantamiento (ITA) disminuye los días abiertos, se escogieron 34 vacas con 80 a 120 días abiertos y ciclando. Se dividieron en dos grupos al azar, uno de 19, a las que se les retiró el ternero durante 72 horas y otro de 15 controles. Todas las vacas pastorearon juntas. La semana previa al experimento, durante la restricción y hasta dos semanas después, se realizaron ecografías y detección de calor. Las variables consideradas fueron la tasa de crecimiento folicular durante el ITA y la tasa de crecimiento del folículo dominante, así como la presentación de calor. El 94.7% de las vacas con ITA presentaron calor durante el tratamiento, o en la semana siguiente, aparentemente ejercieron un efecto social sobre las compañeras sin tratamiento, ya que en estas se presentaron 46.7% de calores simultáneamente. El tratamiento afectó positivamente el diámetro folicular de las vacas tratadas. Palabras clave: amamantamiento, divergencia folicular, ovulación. Summary This study was carried out in suckled Zebu Brahman under low altitude, tropical semi-intensive conditions, characterized by long opened-day periods (>150 days). This low reproductive efficiency is said to be due to suckling that takes place for about 8 months postpartum. 34 cows grazing Brachiaria humidicola were studied, beginning non earlier than 80 days postpartum and all of them presenting follicular dynamics as detected by ultrasonography. The cows were allocated to one of two groups: restricted (19) or non-restricted (15). The restriction consisted of a one- time isolation of calves for 72 hours. During the restriction and for two more days daily ecographic examination was performed. There after the cows were examined ecographically twice a week for two more weeks.. Observation for clinical signs of heat was done twice a day for one-hour period during the restriction and 10 days after. The variables considered were dominant follicular growth at divergency during restriction, and estrus presentation. Effect of restriction on estrus was analyzed with a logistic regression model, and the follicular growth with a general linear model p< 0.05. No significant difference was found in the growth rate of divergent follicles between control and treatment cows (0.87 mm/day vs. 0.93 mm/day). All but one (94.7%) of restricted cows presented heat during the treatment, but interestingly, seven out of fifteen (46.6%) of the control did too, and this was significantly different (p< 0.05). The practical end result is as good as expected but it remains to be determinined why a high unexpected number of control cows did present estrus too. Key words: divergency, ovulation, restriction.